SOSIALISASI DAN EDUKASI DAGUSIBU PADA SISWA SMK AL RAZI SINAR HARAPAN MEDAN JOHOR - Gultom, Evi Depiana (INSTITUT KESEHATAN DELI HUSADA, 2024)
Background: Drug-related health problems in Indonesian society continue to increase over time. The majority of these problems arise because of the public's perspective which does not yet understand the proper and correct use and handling of medicines. The DAGUSIBU drug program is one of the right solutions to overcome this problem. Objective: This service aims to increase the knowledge of students at Al Razi Sinar Harapan Vocational School Medan Johor regarding how to obtain, use, store and dispose of medicines properly. Method: This activity is carried out using an educational method starting from how to use it to the correct disposal of medicines, then interactive discussions, demonstrations as well as eval_uation and monitoring through post tests and pre tests. Results: The socialization activities ran smoothly with participants who were cooperative and enthusiastic in participating in the program. On the other hand, based on the post-test results, it shows that participants better understand the concept of DAGUSIBU medication correctly, so they can minimize errors in drug use. Conclusion: With this socialization, students at Al Razi Sinar Harapan Vocational School Medan Johor can apply the knowledge they have gained to their environment and family.